Risk Factors of Chronic Kidney Disease after Partial Nephrectomy - Makevičius, Jurijus; Kirstukaitė, Beata; Komiagienė, Renata; Želvys, Arūnas; Jankevičius, Feliksas; Miglinas, Marius (Acta medica Lituanica, 2022)
Background: In comparison with radical nephrectomy, partial nephrectomy (PN) is considered a better option for small renal mass surgery, because of optimal kidney tissue removal and parenchyma preservation. But there are patients with worsening postoperative renal function (RF) and chronic kidney disease (CKD) after PN. Therefore, the study aimed to evaluate and detect risk factors for CKD after PN. Materials and Methods. A prospective observational study was conducted, which consisted of 91 individuals who received PN with warm ischemia and an estimated preoperative glomerular filtration rate (eGFR) ≥ 60 ml/min/1.72m2 without pathologic albuminuria. Preoperative and intraoperative factors like intraoperative hypotension (IOH), blood loss, and resected part volume were analyzed. Results. At 6-month follow-up, 14 (15.4 %) patients experienced postoperative CKD. After 12 months of follow-up, 15 (16.5 %) patients had CKD. Patients with CKD had a lower preoperative eGFR than non-CKD group (69.0 vs 91.0 ml/min/1.72m2, p < 0.001), longer ischemia (20.0 vs 14.0, p = 0.002) and IOH time (40.0 (40.0; 47.5) vs 0.0 (0.0; 26.2) min, p < 0.001). Also, higher volumes of resected kidney part tumor and removed parenchyma with higher glomerulosclerosis amounts (73.3 % vs 14.5 %, p = 0.009) were found in CKD group. Estimated blood loss > 500 ml during PN was discovered to be the major risk factor for CKD development (OR 11.13, 95 % CI 1.88–65.92, p = 0.008). Furthermore, kidney resected part volume (OR 1.05, 95% CI 1.05-1.10, p = 0.033) and IOH time (OR 1.11, 95% CI 1.03-1.19, p = 0.005) were identified as risk factors for postoperative CKD. Conclusions. Patients after PN are at an increased risk of CKD development. Most commonly, postoperative CKD occurs in the first 6 months after PN and appears stable after 12 months of follow-up. Blood loss > 500 ml during PN, IOH and resected kidney volume can have an impact on postoperative RF and increase the risk of CKD.